Resilience of low-income Indonesian families during the COVID-19 pandemic: Key factors - Munawaroh, Eem; Sugiharto, Dwi Yuwono Puji; Sofyan, Afriyadi; Nadhirah, Nadia Aulia; Arinata, Firdian Setiya (University of Muhammadiyah Malang, 2025)
The COVID-19 pandemic has severely impacted low-income families, highlighting the critical role of limited resources and unforeseen challenges. The need to remain home for work and study intensified financial strain and increased stress levels. This study aims to identify key factors contributing to family resilience among low-income households during the pandemic. Using a qualitative phenomenological approach, the research was conducted through snowball sampling and in-depth interviews with low-income families in West Java and Central Java, Indonesia. Eleven structured questions guided the interviews, and the transcripts were analyzed using directed content analysis. The findings reveal that flexibility, connectedness, and access to social and economic resources significantly contribute to family resilience. These factors foster collaboration in managing household responsibilities and generating income, suggesting a possible shift away from traditional patriarchal values in Indonesian families. The study offers insights into how these families navigate crises and adapt to changing dynamics, providing a foundation for future research and interventions to enhance family resilience.